Historical demography of the Caribbean spiny lobster Panulirus argus (Latreille, 1804) (Decapoda: Achelata: Palinuridae) in the Florida Keys, USA inferred using single nucleotide polymorphisms (SNPs) - Baeza, Juan Antonio (2019)
The Caribbean spiny lobster Panulirus argus (Latreille, 1804) is an important species in shallow-water coral reefs and target of the most lucrative fishery in the Caribbean Sea. We explored historical demography in P. argus inferred using single nucleotide polymorphisms (SNPs). We expected an increase in population size of P. argus from Florida, USA starting ~18,000-24,000 years ago, after the Last Glacial Maximum, when ice sheets started to retreat and sub-tropical/tropical shallow coastal waters warmed up. A total of 10 lobsters were collected from shallow reefs in the Florida Keys, Florida, USA. One microgram of gDNA extracted from each specimen was used for RAD library construction using established protocols. A panel of 1643 SNPs obtained after interrogation of RAD-tags was used to calculate a site frequency spectrum (SFS). The observed SFS for the Florida population of P. argus exhibited a non-normal distribution peaking at singleton SNPs. The expected SFS in a total of six different candidate demographic models with dissimilar population size changes through time (i.e., standard neutral, exponential growth, bottleneck, bottleneck + growth, two epochs, and three epochs) were numerically computed in the software A i and a model selection approach was implemented to test which expected model(s) best fitted the empirical SFS. The model selection approach indicated that the bottleneck + growth model most closely matched the observed SFS; P. argus experienced a population decline at about 1.9 (0.75-5.7) mya, to then recover and growth exponentially until present time. In disagreement with expectations, population expansion started much earlier than ~18,000-24,000 years ago. Fisheries and conservation studies are expected to profit from the evaluation of genomic and population variability in this species using demographic models, as shown here. Studies exploring population connectivity and locality-specific demographic history of P. argus are underway. © 2019 The Author(s) 2019. Published by Oxford University Press on behalf of The Crustacean Society. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.